O modelo SCOR aplicado no gerenciamento da cadeia de suprimentos: estudo de caso em uma empresa de revenda de peças para motocicletas - VIEIRA, Victor Henrique Souza (2019)
This case study had as main objective to use the Supply Chain Operation Reference (SCOR) model for the supply chain management of a motorcycle parts resale company in the city of Abaetetuba - PA, with the aid of the chain management study supplies, process mappings and 5W1H quality tool. In the course of this work, a model application of SCOR was proposed in the case study. Problems were identified through the processes of level 1,2 and 3 in conjunction with the SCOR metrics in relation to planning, supply, delivery and return of the chain from the company. A new SCOR structure was proposed for the motorcycle parts environment and consequently the solution of the problems identified through level 4 of SCOR. With the use of the presented model, it was possible to verify the company's opportunity to integrate with its processes in a standardized way and to approach its suppliers and customers by creating a strong supply chain, essential characteristic for a competitive differential.